The study of social perceptions about Armenia by digital technologies - A. A. Komarova (Цифровая социология)
The study of social perceptions of Armenia as a tourist destination using digital statistics from Yandex, reviews on tourist sites in conjunction with other sociological methods, such as “content analysis” of newspapers and artworks and questionnaire survey has been carried out. The relevance of sociological research, taking into account digital sources of information, since the Internet is currently the main provider of data on tourist countries, has been substantiated.Tourism in modern Armenia is one of the economic sectors developing at the most intensive pace, and the country is looking for opportunities for further development of this industry, which ensures the practical significance of research related to the image of Armenia and the Armenian people in the eyes of tourists, both real and potential, just planning a trip to this country. The concept of social representations in the concept of Serge Moscovici has been considered. The methodological features of the content analysis method and its limitations have been described. The results of content analysis of Internet sources, as well as publications and cinematic sources on the topic of social representations about Armenia have been presented. The study has revealed stereotypical judgments of tourists who visited and did not visit Armenia. Also of interest is the fact that the main factors influencing the formation of a positive view of Armenia as an object of tourism are tourist awareness of the sights and culture of Armenia and experience of visiting the country. For comparative data analysis, the sample was divided into the following categories of respondents: who visited and did not visit Armenia as tourists, gender, age (two equally filled groups in each category).